CHINA BROADCASTER'S SOCIAL PRESENCE AND AD CONTENT PERSUASIVENESS: MEDIATION ROLE OF AROUSAL AND EMOTION - Liu Shukun; Ooi Kok Loang (International Journal of Accounting, Finance and Business, 2024)
This research explores the intricate dynamics between broadcasters' social presence and the persuasiveness of advertising content in driving impulsive purchasing behavior within China's live-streaming industry. By applying the Elaboration Likelihood Model (ELM) and Emotional Response Theory, this study investigates how cognitive and emotional processes mediate the relationship between persuasive advertising and consumer behavior. The study employs a mixed-methods approach, combining quantitative surveys with qualitative interviews to provide a comprehensive understanding of the factors that contribute to impulsive purchases in the live-streaming environment. Focusing on key urban centers like Beijing and Shanghai, the findings highlight the critical role of social presence, product relevance, and promotional offers in shaping consumer decisions, with arousal and emotion serving as significant mediating factors. The results contribute to the theoretical understanding of consumer behavior in digital contexts and offer practical insights for marketers and advertisers operating in the rapidly evolving Chinese digital landscape.